Performance Evaluation of Semi-Precast Reinforced Concrete Slabs Under Flexural Load - Elbialy, Samy; Youssef , Doaa; Edris, Walid F.; Ghanem, Gouda; Ibrahim, Wael (Salehan Institute of Higher Education, 2025)
This study aims to evaluate the flexural performance of semi-precast reinforced concrete slabs incorporating steel lattice girders as internal reinforcement. The objective is to investigate the influence of geometric and material parameters such as precast slab thickness, lattice girder height, top chord diameter, concrete compressive strength, and the addition of steel or glass fibers on overall flexural capacity and deformation behavior. Thus, previous studies have shown that replacing conventional cast-in-situ slabs with semi-precast systems can reduce total construction costs by 43–70%. Thirteen semi-precast slabs and one control slab were tested under four-point bending, and a nonlinear finite element model was developed in ABAQUS to simulate the experimental response. The analysis focused on load–deflection behavior, strain distribution, and failure modes. Results indicated that increasing slab thickness and chord diameter enhanced stiffness and load-bearing capacity, while higher concrete strength and fiber reinforcement improved crack control and reduced deflection. The FEM model demonstrated strong agreement with experimental results, validating its reliability for predicting structural performance. This study extends previous research by integrating a broad experimental parameter range with a validated ABAQUS finite element model, providing new insights into the structural optimization and cost efficiency of semi-precast slab systems. The proposed semi-precast system exhibited ductile behavior and achieved savings in formwork and labor cost compared with conventional flat slabs, offering a practical and sustainable alternative for efficient concrete construction.